PO.6.136 Systemic lupus erythematosus (SLE): a real world analysis showing significant variance in treatment patterns among 1, 279 systemic lupus erythematosus (SLE) patients in the EU5. (27th September 2022) - Maxine, Y; Ryan, R
Abstract : Purpose: Systemic lupus erythematosus (SLE) patients present significant challenges in management. This study was to uncover real-world treatment patterns among moderate to severely active SLE patients in France, Germany, Italy, Spain, and the UK. Methods: 1, 279 moderate and severe SLE patient records were collected in collaboration with 289 EU5 rheumatologists via an online survey platform from November 12, 2021, through January 28, 2022. Patients were at least 18 years old with diagnosed SLE and treated with at least one prescription agent. Results: While SLE treatments can be varied in the EU5 due to the diversity of the patient population, an unexpectedly high number of treatment combinations were observed among the study cohort. Close to 100 different treatment regimens were reported and a higher prevalence of polypharmacy observed in patients with more severe SLE. Current Regimen Type: Moderate Patients (n=977) | Severe Patients (n=302) Monotherapy: 37% | 28% Dual therapy: 37% | 34% Triple therapy: 20% | 29% Quad therapy: + 5% | 8% The leading treatment among audited patients is monotherapy with HCQ; however, this only accounts for about one-tenth of all patients and is more common among those with moderate disease. Monotherapy belimumab is more prevalent among severe patients, yet these patients are typically on a wide variety of agents, frequently incorporating MTX, HCQ, and steroids. Conclusions: SLE treatment regimens are highly varied in the EU5, with disease severity playing a critical role in the treatment algorithm. Recent approval of anifrolumab in February 2022 is likely to shift the treatment approach even further as rheumatologists settle on ideal patient types for the novel Type 1 interferon inhibitor. Disclosure: Ryan Rex and Maxine Yarnall are employees of Spherix Global Insights, an independent market intelligence firm, and have received no industry funding and report on this study.